El trabajo comunitario como una medida alternativa a la pena privativa de la libertad en ciertas infracciones sancionadas con prisión - González Jaramillo, Flor María (2014)
In the present investigation is fully analyzed and studied what the prison system in Ecuador which is designated as the site where a penalty is purged for having broken the established standard and altered social tranquility, with a critical -reflexive analysis system, idle activities of the defendant within prisons without any merit; and trying to fix on who study this work, which represents and benefits of implementing aid or community work as a form of punishment. The issue raised about this socio- legal issue has great characters is insecurity citizenship and the plight of the jails and prisons of Ecuador, which makes it necessary to implement in the Ecuadorian Criminal Code and related laws for compliance penalties, aid or community work as one of the alternative measures to deprivation of liberty, respecting the constitutional right to personal integrity of the individual, so these rehabilitation centers are an imminent attack this right. In our country increasingly serious problems of both the prison system and how to punish crimes become more evident , it should be noted that it is not necessary to the existence of prisons models, but the correct application of rules and regulations governing both the criminal sanction as the site where you will meet the same, which is why a clear goal to reach is to make a thoughtful critical study of the sentence in the penal decree and its implications, given the overcrowding of which are subject inmates these centers , formulating an approach that is consistent with the social reality in which we live as the lack of implementation of community service as an alternative to deprivation of liberty as cause serious social problems because they do not meet a beneficial rehabilitation and greater public safety, no internal comply with the legal regime of rehabilitation through workshops , education , fostering the spirit of awareness of the damage caused.